Pandangan Gen Z Terhadap Pemanfaatan Gaming Mobile Legends sebagai Peluang Sumber Penghasilan: Gen Z's Views on the Use of Mobile Legends Gaming as an Income Opportunity - Nurul Karisma; Yovita Eka Wulandari; Shelvi Amalia Putri (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
This article aims to analyze the views of Generation Z (Gen Z) towards the use of Mobile Legends online game as a source of income. This research uses a qualitative approach with a case study method involving six research subjects aged 20-24 years old and actively playing Mobile Legends. Data were collected through semi-structured interviews, observations, and documentation studies. The results showed that Gen Z has a positive view of Mobile Legends as a source of additional income. Their main motivations are the desire to earn extra income, an income-generating hobby, filling spare time, and entrepreneurial opportunities. The strategies used include selling accounts, becoming a jockey, live streaming, content creation, and participating in tournaments. Challenges faced include fierce competition, meta game changes, risk of fraud, and the need to maintain a balance between gaming and real life. Playing intensity has a relationship with monetization success, but excessive intensity can have a negative impact. This research provides new insights into the phenomenon of online game utilization as a source of income among Gen Z and its implications for the digital economy and entrepreneurship.